(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deols with the project work, components, processes and stages of it. Basic principles and reflections of such methods in language teaching have fully been stated. Main Methodological and theoretical approaches of project work have been clearly analyzet.